2019
DOI: 10.1007/s00402-019-03166-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive posterior correction of Lenke 5C idiopathic scoliosis: comparative analysis of minimal invasive vs. open surgery

Abstract: Introduction Surgical management of adolescent idiopathic scoliosis in spite of usually favourable outcomes is still a major operation. Therefore, efforts are being undertaken to minimalize the procedure, reduce the surgical trauma and postoperative convalescence. The study was designed to compare posterior minimal invasive surgery using navigation based on intraoperative 3D imaging and standard open instrumented fusion in Lenke 5C idiopathic scoliosis treatment. Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…This suggests that MIS is as good as the open surgery technique in attaining multilevel vertebral fusions. Urbanski et al [ 17 ] showed a significant difference in the number of days opioids were required, with a shorter period in the MIS group. Sarwahi et al [ 15 ] showed no difference between the two groups in opioid requirements, and our analysis favored the MIS group in this parameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that MIS is as good as the open surgery technique in attaining multilevel vertebral fusions. Urbanski et al [ 17 ] showed a significant difference in the number of days opioids were required, with a shorter period in the MIS group. Sarwahi et al [ 15 ] showed no difference between the two groups in opioid requirements, and our analysis favored the MIS group in this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Sarwahi et al [ 15 ] showed no difference between the two groups in opioid requirements, and our analysis favored the MIS group in this parameter. Gómez et al [ 16 ] and Sarwahi et al [ 15 ] showed a short duration of stay in the open surgery group, whereas Miyanji and Desai [ 14 ] and Urbanski et al [ 17 ] showed a shorter stay in the MIS group. Our analysis showed no difference between both groups in this parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Navigation based on intraoperative 3D imaging can help to achieve more precise instrumented fusion. 8…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, the operative blood loss was 218.3 ± 17.1 mL with a corrected angle of 76.1 ± 11.1 as compared to that published by other authors who had an operative blood loss of 138.75 ± 50.04 mL with corrected angle of 68.25% ± 6.1 %. 8 In reduction of the volume of bleeding, different additional methods can also play a role, including the use of hemostatic agent tranexamic acid or special techniques. 20 These modifications of surgical techniques applied to reduce tissue injuries and blood loss were offered, including endoscope-assisted spinal surgery.…”
Section: Discussionmentioning
confidence: 99%